Shaped charge simulation using SPH in cylindrical coordinates. Issue 2 (20th April 2015) - Baêta-Neves, Alessandro Piccaglia; Ferreira, Arnaldo
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to investigate the applicability of the smoothed particle hydrodynamics (SPH) method in the jet formation process of a cylindrical-shaped charge (CSC). Different SPH formulations, suggested in other works, to other applications, are brought together in order to build a model that represents the phenomenon of detonation of a CSC in a more realistic way. Design/methodology/approach – A two-dimensional (2D) SPH formulation using cylindrical coordinates is adopted to simulate CSCs. The problem of fluid-solid interaction between the detonation wave of the explosive and the metal liner, numerically unstable due to the great difference in density between the phases, is resolved adopting the multi-phase strategy. A new proposition of artificial viscosity is incorporated in order to account the convergence effect of the liner particles toward the axis of symmetry of the charge. Two numerical examples are used to validate the formulation. In the first, the velocity and length differences between the jets formed from a CSC and a linear-shaped charge (LSC) using planar detonation on both are compared. In the second example, the effect of the conical cavity angle in the maximum jet velocity is evaluated, comparing the simulated results of CSC with four different cavity angles, with the experimental results. Findings – The results show that the 2D SPH method in cylindrical coordinates is able to simulate the detonation process of a CSC. Accordingly with the formulations used, the following conclusions can be made: the multi-phase strategy is able to capture the multi-material interface of the fluid-solid interaction between the detonation wave and the metal liner; and in the cylindrical geometry, a second artificial viscosity is necessary in order to include the convergence effect of the particles toward the axis of symmetry and obtaining more realistic results for the jet velocity. Originality/value – The applicability of the SPH method to simulate LSCs has been tested and verified in other works, but there are not references that address the application of the SPH method to simulate CSCs. CSCs are widely used in the defense industry and in the oil industries. In the oil industry, the perforating process may currently be the most common use of such a device. For this reason, it is believed that the proposed formulation in this paper is a good alternative to these specific applications.